State feedback guaranteed cost controller for nonlinear time-varying delay systems - Niamsup P. (Springer Science + Business Media, 2015)
© Vietnam Academy of Science and Technology (VAST) and Springer Science+Business Media Singapore 2014. This paper considers the problem of designing state feedback guaranteed cost controllers for a class of nonlinear systems with time-varying delay. The time delay is a continuous function belonging to a given interval and not required to be differentiable. By applying Lyapunov function method and linear matrix inequality (LMI) technique, new delay-dependent sufficient conditions for designing the state feedback guaranteed cost controller are derived. The method is also extended to handle system uncertainties in a straightforward way. A numerical example is given to illustrate the design procedure.